The genus Anathallis (Orchidaceae: Pleurothallidinae) in Mexico - Solano Gómez, Rodolfo
Anathallis encompasses nearly 120 neotropical orchid species, with Mexico representing the northernmost limit of its distribution. Around fifteen Mexican species were initially classified in Anathallis during the current century. However, several of them have been reclassified in recent years into Lankesteriana, Specklinia, and Stelis. Currently, Anathallis in Mexico includes A. greenwoodii, A. lewisiae, A. minutalis, A. oblanceolata, A. sertularioides, and A. yucatanensis. This work presents the taxonomic treatment for these species, models of their potential distribution, and the assesses of their conservation status in Mexico. For this, specialized literature, living and herbarium specimens, and online databases were examined. For each species, a description, drawing, photograph, and distribution map were prepared, along with information on nomen-clature, habitat, phenology, comparison with similar species, and an assessment of their risk status is provided. Mexican Anathallis plants are characterized by their diminutive habit, rhizomatous growth, semi-open flow-ers with acute sepals and petals, free lateral sepals, mobile lip, and winged column. Five species are recognized among them: A. lewisiae, A. minutalis, A. oblanceolata, A. sertularioides, and A. yucatanensis. Anathallis greenwoodii exhibits a morphology more similar to Lankesteriana and it was transferred accordingly. Anathallis oblanceolata was previously known only from the type locality and is redescribed based on specimens previously confused with A. minutalis. Both species are endemic to the mountainous regions of Mexico. Anathallis lewisiae,A. sertularioides, and A. yucatanensis grow in warm, lowland areas along the Gulf of Mexico coast and Yucatan Peninsula. The extinction risk assessment assigned the category of species subject to special protection to the five Mexican taxa. For each taxon the extent of its distribution in Mexico and the environmental variables determining...